Establishing government municipal archives case studies of local government archives' practices - Garcia, Justina P.; Aguirre, Vyva Victoria M.; Rey, Emma M.; Arlante, Salvacion M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The case study focused on six local government units from different regions which successfully established their archives. An interview questionnaire using a combination of open-ended and structured questions was developed by the researcher.
The study aimed to determine the following: 1) the successfully established archives of the local government units; 2) establishment of archives pursuant to the Local Government Code of 1991, Sec. 374; 3) the local government units' practices in establishing archives with regards to mandate or authority, archives policy, archives services, and management and administrative support; 4) difficulties, problems, or failures in establishing archives; 5) successes in establishing archives; and 6) best practices in establishing their archives. Qualitative method of research was used to determine the objectives of the study.
Results of the study reveal the following: 1) There are two successfully established local government archives from the National Capital Region (Archives Section of the City Secretary's Office of Quezon City, and Barangay Capri Archives, Novaliches, Quezon City); three from Region I (Archives Division of the General Service Office (GSO) of the Province of Pangasinan situated in Lingayen; Dagupan City Archives; and Archives of the Office of the Secretary to the Sangguniang Panlungsod, City of San Fernando, La Union); and one from Region X (Lugait Library, Archives, Museum and Information Center, Misamis Oriental) that were evaluated in this study. 2) All of the six local government units established their archives pursuant to the Local Government Code of 1991, Sec. 374.3). The local government units enacted different rulings such as ordinances, executive orders, Sanggunian resolutions, or relied on the Local Government Code of 1991 as their mandate. Most of the local government archives are compliant with archives policy, and properly execute practices in establishing archives with regards to archives services. Most of the local government units gained management and administrative support to establish their archives. 4) Inadequate space, lack of funds and knowledge in archiving, and conflicts in implementation were the major problems encountered in establishing the archives. Failures occurred because lack of funds and conflicts in implementation not completely dealt with. 5) Success in establishing the archives was achieved by all the local government units by applying different strategies and techniques such as: the mandate of the Local Government Code of 1991 and creation of other orders relating to the establishment of archives; management support; initiative, perseverance and teamwork of people involved; and attendance to trainings and consultations with the Society of Filipino Archivists, Inc. (SFA). 6) Best practices in establishing archives were identified in all the local government archives with regards to mandate or authority, archives policy, and archives services. However, in terms of management and administrative support, only three local government archives have best practices. In dealing with problems and difficulties in establishing the archives, only five local archives exhibited best practices.
Several recommendations were drawn from the analysis of best practices in establishing the local government archives, which can be adopted in establishing municipal archives.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Local government -- Philippines -- Archives